Digital Multivocality and Embodied Language in Theatrical Space - Darroch, Michael (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2008)
AbstractThis paper investigates the changing relation of the human voice to theatrical space. Innovations in digital sound technologies are reconfiguring the materiality of the voice and, consequently, the mediality of contemporary theatre. Western theatre, which developed alongside the shift from an oral to a visually-oriented, literate society, has largely remained a visual medium that continually subsumes orality. New media of the 19th and 20th centuries prompted various proposals for a “total theatre,” which generally worked towards removing voice and language from the theatrical environment. Drawing upon the recent multivocal works of Quebec artist Marie Brassard, the author proposes that today’s digital sound technologies are redrawing the possibilities for voice in a theatre that enables, in McLuhan’s terms, the constant “interplay of the senses” within a new acoustic space.